Pilot study on longitudinal change in pancreatic proton density fat fraction during a weight‐loss surgery program in adults with obesity. Issue 4 (30th January 2019) - Covarrubias, Yesenia; Fowler, Kathryn J.; Mamidipalli, Adrija; Hamilton, Gavin; Wolfson, Tanya; Leinhard, Olof Dahlqvist; Jacobsen, Garth; Horgan, Santiago; Schwimmer, Jeffrey B.; Reeder, Scott B.; Sirlin, Claude B.
Abstract : Background: Quantitative‐chemical‐shift‐encoded (CSE)‐MRI methods have been applied to the liver. The feasibility and potential utility CSE‐MRI in monitoring changes in pancreatic proton density fat fraction (PDFF) have not yet been demonstrated. Purpose: To use quantitative CSE‐MRI to estimate pancreatic fat changes during a weight‐loss program in adults with severe obesity and nonalcoholic fatty liver disease (NAFLD). To explore the relationship of reduction in pancreatic PDFF with reductions in anthropometric indices. Study Type: Prospective/longitudinal. Population: Nine adults with severe obesity and NAFLD enrolled in a weight‐loss program. Field Strength/Sequence: CSE‐MRI fat quantification techniques and multistation‐volumetric fat/water separation techniques were performed at 3 T. Assessment: PDFF values were recorded from parametric maps colocalized across timepoints. Statistical Tests: Rates of change of log‐transformed variables across time were determined (linear‐regression), and their significance assessed compared with no change (Wilcoxon test). Rates of change were correlated pairwise (Spearman's correlation). Results: Mean pancreatic PDFF decreased by 5.7% (range 0.7–17.7%) from 14.3 to 8.6%, hepatic PDFF by 11.4% (2.6–22.0%) from 14.8 to 3.4%, weight by 30.9 kg (17.3–64.2 kg) from 119.0 to 88.1 kg, body mass index by 11.0 kg/m 2 (6.3–19.1 kg/m 2 ) from 44.1 to 32.9 kg/m 2, waist circumference (WC) by 25.2 cm (4.0–41.0 cm) from 133.1 to 107.9 cm, HC by 23.5 cm (4.5–47.0 cm) from 135.8 to 112.3 cm, visceral adipose tissue (VAT) by 2.9 L (1.7–5.7 L) from 7.1 to 4.2 L, subcutaneous adipose tissue (SCAT) by 4.0 L (2.9–7.4 L) from 15.0 to 11.0 L. Log‐transformed rate of change for pancreatic PDFF was moderately correlated with log‐transformed rates for hepatic PDFF, VAT, SCAT, and WC (ρ = 0.5, 0.47, 0.45, and 0.48, respectively), although not statistically significant. Data Conclusion: Changes in pancreatic PDFF can be estimated by quantitative CSE‐MRI in adults undergoing a weight‐loss surgery program. Pancreatic and hepatic PDFF and anthropometric indices decreased significantly. Level of Evidence: 2 Technical Efficacy Stage: 1 J. Magn. Reson. Imaging 2019;50:1092–1102.